Digitalisasi Hadis dalam Sastra Komik Islami di Media Sosial Instagram @akhlaqpedia - Mudhofar, Afif; Ubaidillah (Fakultas Dakwah dan Ilmu Komunikasi, Universitas PTIQ Jakarta, 2025)
The development of digital technology has had an impact on the decline of religion, especially seen in the moral degradation of the younger generation due to violations of norms and ethics of politeness. Nowadays, social media can be used as a da'wah weapon to spread knowledge, both in terms of academics and religiosity. For example, the Instagram account @akhlaqpedia attracts attention by sharing Islamic comics that highlight various hadiths. The aim of this research is to enrich the study of living hadith on social media, especially Instagram. The discussion regarding Instagram social media is very poorly studied. The method used in the research is library research with reception theory introduced by Ahmad Rafiq, referring to three steps, namely exegesis, aesthetics and functional. This research found that the hadith in the Islamic comic content @akhlakpedia are presented in a simple, unique, easy to understand manner and use everyday language. This has become one of the hadith literatures to increase people's piety so that they can accept the hadith and apply its contents as described.